The evolution of malaria at Loreto Region - Celis S., Juan (2003)
Objectives: To describe the evolution of malaria at the Loreto Region, comparing vivax with falciparum malaria, its evolution in comparison with the rest of Peru and the changes in medicinal policy. Material and methods: Observational and descriptive study. The Ministry of Health General Epidemiology Office was the source of information. Results: Both vivax and falciparum malaria incidence at the Loreto Region has increased since 2000, following a reduction of 40%. An increase of 24% was reported in 2001 with respect to 2000 and 52% in 2002 with respect to 2001. As a percentage of all cases in Peru, Loreto accounted for 29%, 31%, 44%, 47% and 57%, respectively, in the years 1998 through 2002. Loreto has been at high risk since 1995. In 2003 at the 46rd Epidemiology Week (09th – 15th November) Loreto (IPA 45) and San Martin (IPA 10) were placed at high risk; 60,4% of all cases come from Loreto. Conclusions: Loreto Region malaria incidence has been increasing in the last 3 years. Peruvian cases of malaria in the last few years have been centered at the Loreto Region.